Odpowiedzi

2010-04-14T15:06:45+02:00
2/3 a - 2/5 b - a + b = dla a=6, b=5
= (2/3a-a) - (2/5b-b) =
= -1/3a - (-3/5b) =
= -1/3 * 6 + 3/5 * 5 =
= -2+3 = 1

5a+3(a-b) - 14 a = dla a=2, b + -1
5a+3a-3b-14a =
= -6a-3b =
= -3(2a+b) =
= -3(2*2 + (-1))=
= -3(4-1) =
= -3 * 3 = -9
2010-04-14T15:10:27+02:00
2/2a-2/6b
1a-3b
6-15=-9

5a+3(a-b)-14a
5a-3a-3b-14a
2a-3b-14a
-12a-3b
-24-3=-27
2010-04-14T15:12:31+02:00
2/3a-2/5b-3/3a+5/5b
-1/3a+3/5b

-1/3*6+3/5*5
-2+3=1


5a+3a-3b-14a
-6a-3b
-6*2-3*(-1)=-12-(-3)=-9